ANALISIS POTENSI FINANCIAL DISTRESS DENGAN METODE SPRINGATE PADA BANK UMUM SYARIAH DI INDONESIA - Marlinda, Desi; Yulia, Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research aims to know the potential financial distress with Springate method at sharia banks in Indonesia. Financial ratios used is the ratio of working capital to total assets, the ratio of earnings before interest and taxes to total assets (EBIT/Total assets), the ratio of earnings before taxes to total current liabilities (EBT/current liability), and the ratio of sales to total assets. The method used in this research is quantitative research with descriptive study purposes. Data used is secondary data, in the form of an annual financial statement data sharia banks 2014-2018 period. The data analysis is done by using the method of calculation of financial ratios Springate, data is processed using a computer device tools Microsoft Excel. The results of this study indicate that all Islamic banks in the span of the last five years the average is in the category are not experiencing finan cial distress. In the calculation method Springate, 11 Islamic Banks (BUS) in Indonesia during the period 2014 to 2018 shows that only three Islamic banks that are in the unhealthy category predictions that the Bank BRI Syariah, Bank Syariah Muamalat and Bank Syariah Bukopin.